Effectiveness of Online Learning with Services in Improving PAI Learning Achievement - Atik Rusdiani; Joni Putra (Edumaspul: Jurnal Pendidikan, 2024)
The purpose of this research is to find out about the effectiveness of online learning with Google services in improving PAI learning achievement in SD Natar sub-district. And is expected to: 1) Produce information related to the implementation of online learning in PAI subjects in elementary schools in Natar sub-district, 2) Provide knowledge of effective electronic digital utilization in online learning in PAI subjects in elementary schools in Natar sub-district properly, 3) Foster awareness of the importance of electronic media in the implementation of online learning, which is expected to encourage PAI teachers to implement electronic media properly. This research method using this is descriptive quantitative. And the population is all elementary schools in Natar sub-district with a research sample of 20 students. The data that has been collected is then analyzed using descriptive statistics. The conclusion of this study is that the effectiveness of online learning with google services in PAI subjects in Natar sub-district elementary schools can improve student learning achievement, 75% of learning outcomes are complete and reach KKM.